Naskah Melayu dengan Nama dan Tokoh Perempuan - Dewaki Kramadibrata (HISKI, 2007)
This paper discussed Malay manuscripts which titled with womens' name and they also conduct as the heroine. The heroine, for example Siti Zawiyah and Siti l lasanah, were described as a beautiful lady, kind hearted, and very obedient to God. Meanwhile, Siti Zuhrah (she disguised as a man) was described as an ideal llcro.